Comunicação gráfica em interfaces de hipermídia de educação a distância via web - Burgos, Taciana de Lima (2010)
This study aims to analyze the communication graphics of layouts of hypermedia interfaces oriented to Distance Education via the Internet. This proposal is justified by widening the offer of courses that modality and the consequent application of items of hypermedia for teaching-learning. The method of analysis involved the search nethnographic, addressed to the cycle student intermediary of the Training Program Continuing Medias in Education, and the evaluation heuristic of the interfaces of Virtual Learning Environment "E-Proinfo" and of the modules of the Cycle. This evaluation we observed the implementation of the attributes of usability and the degree of interactivity of each interface. The results revealed an inefficient implementation of the attributes of usability, which meant a consequent reduction of the levels of interactivity. As proposing the present Design Virtual Learning, a model of hypermedia layout, designed to generate usability for Virtual learning environments and extend the acquisition of literancy for students and tutors. This proposal design not hypermedia aims the demarcation of models pre-conceived, but the proposal of layout in which each element of hypermedia is applied with a view to generate a seaworthiness intuitive, more agile and efficient, in these ambients